Tissue acquisition and pancreatic masses: Which needle and which acquisition technique should be used? - Mangiavillano, Benedetto; Sosa-Valencia, Leonardo; Deprez, Pierre; Eisendrath, Pierre; Robles-Medranda, Carlos; Eusebi, Leonardo H.; Di Leo, Milena; Auriemma, Francesco; Bianchetti, Mario; Anderloni, Andrea; Carrara, Silvia; Repici, Alessandro (Endoscopy International Open, 2020)
Background and study aims Pancreatic cancer represents the fourth most common cause of cancer-related deaths in Western countries and the need of a low-risk investigation to obtain an accurate histopathological diagnosis has become increasingly pressing. Endoscopic ultrasonography (EUS) with fine-needle aspiration (FNA) is the standard method for obtaining samples from pancreatic masses. In recent years, there has been an increasing need to obtain histological specimens during EUS procedures, rather than cytological ones, to guide oncological treatment options, leading to the so-call “FNB concept.” Different needles have been developed for fine-needle biopsy (FNB) in recent years, enabling acquisition of larger specimens on which to perform histological and molecular analyses. The aim of this narrative review was to assess the role of EUS-guided FNA and FNB in patients with pancreatic masses, and to identify which needle and which acquisition technique should be used to improve tissue acquisition.